Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1989
DOI: 10.1002/jnr.490240303
|View full text |Cite
|
Sign up to set email alerts
|

Denervation and hyperinnervation in the nervous system of diabetic animals. I. The autonomic neuronal dystrophy of the gut

Abstract: Peripheral neuropathy is a correlate of experimental diabetes induced in rats by means of a single injection of alloxan. The autonomic and enteric innervation of the gut are profoundly affected in the small intestine of such animals. A complex process of denervation and hyperinnervation of the gut wall of diabetic animals is observed. It was previously reported that the cholinergic parasympathetic innervation of the intestine is markedly reduced. We have found that noradrenergic sympathetic axons hyperinnervat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

1989
1989
2010
2010

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 38 publications
(19 citation statements)
references
References 40 publications
1
18
0
Order By: Relevance
“…Substance P is supplied to the gastrointestinal tract mainly by intrinsic innervation arising from myenteric and submucosal plexi (Pernow, 1983). Our data confirm previous suggestions of enteric nerve pathology in the gut of diabetic animals (Lincoln et al, 1984;Di Giulio et al, 1989a). The protective effects of ALCAR treatment reported in this paper confirm previous results suggesting a remarkable effect of such a pharmacological treatment upon peptide alterations observed in the gut of diabetic rats.…”
Section: Discussionsupporting
confidence: 95%
“…Substance P is supplied to the gastrointestinal tract mainly by intrinsic innervation arising from myenteric and submucosal plexi (Pernow, 1983). Our data confirm previous suggestions of enteric nerve pathology in the gut of diabetic animals (Lincoln et al, 1984;Di Giulio et al, 1989a). The protective effects of ALCAR treatment reported in this paper confirm previous results suggesting a remarkable effect of such a pharmacological treatment upon peptide alterations observed in the gut of diabetic rats.…”
Section: Discussionsupporting
confidence: 95%
“…In more chronic diabetes, the nerve content of substance P is also reduced (Robinson et al, 1987). The peptidergic loss also occurs in the gastrointestinal system, where the content of metenkephalin, calcitonin gene-related peptide (CGRP), and substance P progressively decreases in diabetic rats (Gorio et al, 1992;Di Giulio et al, 1989;Belai et al, 1987). It has also been reported that in skin biopsies of chronic diabetic patients affected by sensory loss and hypo-aesthesia, there is a reduction in the density of substance P immunocytochemically stained nerve fibers (Levy et al, 1992).…”
Section: Discussionmentioning
confidence: 97%
“…There are indeed good correlations between biochemical changes of axonal transport and morpho-functional alterations, e.g., axonal atrophy and changes of conduction velocity (Vitadello et a]., 1983(Vitadello et a]., , 1985Gorio et al, 1984;Norido et al, 1984). The innervation of the gut is also deeply affected by diabetcs with specific changes in peptidergic and monoaminergic levels (Di Giulio et al, 1989a). We have also shown that the central nervous system may also be affected in diabetic animals (Di Giulio et al, 1989b).…”
Section: Gtpy S C O N C E N T R R T I O N [ M Imentioning
confidence: 90%
“…Substance P (SP), vaso-active intestinal peptide (VIP), and met-enkephalin (ME) levels were determined with radioimmunoassay (RIA) as previously reported (Di Giulio et al, 1989a).…”
Section: Monoamine and Peptide Assaysmentioning
confidence: 99%